Meaning Of The Use Of Gadgets On Women Students In Industrial Era 4.0: Makna Pemanfaatan Gadget Pada Mahasiswa Perempuan Di Era Industri 4.0 - Genisa, Oktin; Situmorang, Nina Zulida; Junianto, Mahmud; Basman, Fadhilah Auliyah (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this research is to learn how to use gadgets for students in the industrial era 4.0. The research method used is qualitative using indigenous psychology. The research subjects were students in the Yogyakarta Special Region who examined 70 female students. The results in this study were female students who used the highest category of communication by 25%, followed by 17% knowledge, 17% practical, 15% entertainment, 14% information, 5% archives, 4% business and 3% sharing.